Patient Outcomes After Transolecranon Fracture-Dislocation. Issue 3 (1st February 2021) - Haller, Justin M.; Hulet, D. Andrew; Hannay, William; Cardon, Jeffrey; Tashjian, Robert; Beingessner, Daphne
Abstract : Introduction: There are few small case series that discuss patient outcomes after a transolecranon fracture-dislocation, and they suggest that patients have reasonable function after injury. The purpose of this study was to describe the injury pattern and clinical outcomes of transolecranon fracture-dislocations. Methods: After Institutional Review Board approval, transolecranon fracture-dislocations treated at two academic level 1 trauma centers between 2005 and 2018 were retrospectively reviewed. Fracture characteristics and postsurgical complications were recorded. Radiographs were reviewed for arthrosis, and Quick Disabilities of Arm, Shoulder, and Hand (QuickDASH) scores were obtained at a minimum of 12 months after injury. Results: Thirty-five patients with a mean follow-up of 28 months (range, 12 to 117 months) were included. Nine patients had associated radial head fracture, 23 patients had associated coronoid fracture, four patients had ligamentous injury, and two patients had capitellum fracture. Four patients (11%) developed infection and required irrigation and débridement with intravenous antibiotics. Thirteen patients (13 of 35, 37%) developed radiographic arthrosis with most (11 of 13) having grade 2 or three changes. Patients who had associated radial head fracture, coronoid fracture, capitellum fracture, and/or ligamentous injury had significant arthrosis (10 of 24, 42%) more commonly than patients with olecranon fracture alone (1 of 11, 9%) ( P = 0.05). Twenty-eight patients completed patient outcomes instrument and achieved a mean QuickDASH score of 9 (range, 0 to 59). Patients with isolated transolecranon fracture had a significantly better QuickDASH score (0.93, 0 to 4) than patients with transolecranon fracture variant with associated coronoid fracture, radial head fracture, distal humeral fracture, or ligamentous injury (11.74, 0 to 59) ( P = 0.04). Discussion: Patients with transolecranon fracture-dislocation had excellent return to function based on the QuickDASH outcome assessment. Patients with transolecranon fracture with associated radial head fracture, coronoid fracture, humeral condyle fracture, and/or ligamentous injury tend to have worse functional outcome than patients with simple transolecranon fracture. Level of Evidence: Level IV-case series